Modeling the experience of Iranian telecommunication company customers from commercial sales in line with their sustainability - Mohammad Karvand; Mahdi Mahmodzadeh; Hossein Hakimpour; Monireh Salehnia (ارزش آفرینی در مدیریت کسب و کار)
Abstract The purpose of this research is to model the experience of customers of Iran Telecommunications Company from commercial sales in line with their sustainability. According to its purpose, the research method is applicable, qualitative in terms of the approach, and descriptive-exploratory in terms of the way of analyzing the data, with the phenomenology method. The statistical population of the research consists of 17 special customers of commercial telecommunications services with more experience of using these services, selected by the purposeful sampling method. A semi-structured interview was used to collect information. Data analysis was done using the theme analysis approach manually and coding. The results showed that the categories and components that make up the customer experience in line with their sustainability consist of 9 categories and 26 elements including: operational prerequisites of customer experience management (strategic prerequisites, human prerequisites, and technical prerequisites), measurement and analysis of customer experience (collecting and recording customer experiences, analyzing customer experiences, interpreting customer experiences, and monitoring customer experience performance), service delivery experience (network quality, service delivery quality, and emotional effect), value co-creation (customer participation in value creation, service personalization, and customer relationship management), profitability (customer share, customer loyalty, and customer satisfaction), marketing mix (price, place, product, and promotion), brand image (brand reputation and social responsibility), supportive activities (complaint management and after-sales service), and barriers to brand switching (the nature of the company and switching costs). Extended Abstract Introduction By passing the economy of raw materials, goods and services, and entering the new era, which is the economy of experience; the success of businesses is not only dependent on providing services and products, but also on the creation of experience. Nowadays, instead of services and products, memorable experiences are sold, and creating excellent customer experience is the main goal of organizations in various industries, especially customer-oriented industries. Professionals have accepted the limitations of traditional marketing approaches based on components such as price, product and quality, and believe in the importance of customer experience in achieving competitive advantage and creating customer loyalty (Hwang & Seo, 2016). In other words, we have entered the new era of the customer, an era where the authority in production and distribution or information expertise is no longer a competitive advantage and has turned into a commodity, but the choice of customers is the main differentiator, and organizations should focus on customer experience management (Plessis & Vries, 2016). Customer experience is a term that explains the collective interaction of a customer with a service provider and also helps determine the durability of that customer's relationship with the service provider (Bhatti et al, 2016). In today's competitive environment, negligence in customer service or service quality can lead to customer loss, which is not cost-effective to acquire new customers, and developing preventive strategies to retain customers is very important (Kaur & Sharma, 2015). Customer retention can be considered a part of marketing strategy. By keeping current customers, businesses can reduce customer churn and the costs associated with attracting new customers, which contributes to long-term profitability and sustainable competitive advantage. Therefore, customer retention is not just a reactive strategy, but a strategic approach that can directly affect the company's market share and profit (Zhang et al, 2024). In recent decades, many companies have considered customer retention as an important principle in their management and marketing decisions, and organizations have realized that keeping current customers is cheaper than attracting new customers (Taghavifard et al, 2017). Therefore, the main problem that this research seeks to answer is: how is the modeling of the experience of customers of the Iranian Telecommunication Company from commercial sales in line with their sustainability? Theoretical Framework Customer experience Customer experience has become a central topic in marketing research as businesses increasingly realize that their success depends largely on providing positive shopping experiences to their customers (Chen & Yang, 2021).